Body Composition and Bone Mineral Density in Patients With Heart Failure. (April 2017) - Abshire, Demetrius A.; Moser, Debra K.; Clasey, Jody L.; Chung, Misook L.; Pressler, Susan J.; Dunbar, Sandra B.; Heo, Seongkum; Lennie, Terry A.
The purpose of this study was to examine associations among bone mineral density, osteopenia/osteoporosis, body mass index (BMI), and body composition in patients with heart failure (HF). A total of 119 patients (age = 61 ± 12 years, 65% male) underwent dual-energy X-ray absorptiometry scans to determine bone mineral density and body composition. In multivariable linear regressions, BMI, relative skeletal muscle index (RSMI), and mineral-free lean mass were positively associated with total body bone mineral density. Mineral-free lean mass was most strongly associated with bone mineral density (β = .398). In multivariable logistic regressions, higher BMI, RSMI, and mineral-free lean mass were associated with lower odds for osteopenia/osteoporosis. Fat mass was not associated with total body bone mineral density or osteopenia/osteoporosis. These results suggest that muscle mass may be the important component of body mass associated with bone mineral density in patients with HF.